2015
DOI: 10.1089/ham.2014.1086
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Concentrations of Hypoxia Inducible Factor Responsive Proteins and Excessive Erythrocytosis in High Altitude Peru

Abstract: Painschab, Matthew S., Gary E. Malpartida, Victor G. Davila-Roman, Robert H. Gilman, Todd M. Kolb, Fabiola Leon-Velarde, J. Jaime Miranda, and William Checkley. Association between serum concentrations of hypoxia inducible factor responsive proteins and excessive erythrocytosis in high altitude Peru. High Alt Med Biol 16:26-33, 2015.-Long-term residence at high altitude is associated with the development of chronic mountain sickness (CMS), which is characterized by excessive erythrocytosis (EE). EE occurs unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…In the plateau region, the long-term adaptation and natural selection of modern Tibetan and Han changed their genetic structure [ 19 ]. Chronic hypobaric hypoxia is the main reason of HAPC [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the plateau region, the long-term adaptation and natural selection of modern Tibetan and Han changed their genetic structure [ 19 ]. Chronic hypobaric hypoxia is the main reason of HAPC [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CMS have inappropriately elevated or normal EPO concentrations in relation to their polycythemia. 79 CMS prevalence varies depending on ethnic groups. In the Andes, the prevalence is highest and increases with age and altitude of residence.…”
Section: 77mentioning
confidence: 99%
“…In Puno, a highland Peruvian area located at 3825 m above sea level, our international team of researchers showed that excessive erythrocytosis was strongly associated with having metabolic syndrome and being overweight, besides its association with hypoxemia and lower forced vital capacity [ 43 ]. Other high altitude research includes investigations of biomarkers linked to excessive erythrocytosis [ 44 ], use of point-of-care devices for screening of excessive erythrocytosis [ 45 ], and studies of the link between hypoxemia and cardiometabolic conditions [ 46 ].…”
Section: Reviewmentioning
confidence: 99%